AI-Driven Career Pathways: Predictive Counseling Systems for Aligning Student Potential with Future Job Markets - Loso Judijanto; Herryansyah Herryansyah; Seno Lamsir (Journal of Paddisengeng Technology, 2025)
Background. Rapid technological advancements and evolving labor markets have created significant challenges in aligning students’ academic pathways with future career opportunities. Traditional counseling approaches often lack predictive capacity, leaving students underprepared for emerging job sectors. Artificial Intelligence (AI)-driven predictive counseling systems offer new possibilities by integrating student potential, skills, and aspirations with real-time labor market trends. Purpose. This study aims to examine the effectiveness of AI-driven career counseling systems in predicting and aligning student potential with future job markets. Specifically, it explores the extent to which AI-based predictive models can enhance the accuracy of career guidance and reduce mismatches between educational outcomes and employment demands. Method. Using a quantitative design, the research collected data from 312 university students across three institutions in Indonesia. Students engaged with an AI-powered career counseling platform that generated personalized career recommendations based on academic performance, psychological profiling, and labor market analytics. Data were obtained through system usage logs, surveys, and follow-up evaluations. Statistical analyses, including regression and ANOVA, were employed to assess the impact of AI counseling on student decision-making and career clarity. Results. Findings reveal that AI-driven counseling significantly improves students’ career awareness and alignment with future labor demands. Students using the predictive system demonstrated higher confidence in their career choices and reduced anxiety about employability. Additionally, the AI system identified potential career trajectories in emerging sectors, such as digital finance, green technologies, and AI ethics, which were often overlooked in traditional counseling. Conclusion. The study underscores the transformative role of AI in educational counseling, emphasizing its potential to bridge gaps between academic preparation and job market realities. Implementing predictive AI models in career services can empower students to make informed choices, while enabling institutions to adapt curricula to future workforce needs.